Mesh Repaire of Inguinal Hernia- A Novel Approach Through Superficial Inguinal Ring - Subrahmanyam, M.; Spandana, V. V.; Rajkumar, S. (British Journal of Healthcare and Medical Research, 2026)
Background : Mesh repair of inguinal hernia is the standard procedure with recurrence rate 0.5%. An oblaique inguinal incision of4-5 cm. is used for the open mesh repair. This needs inguinal canal to be opened after incising the external oblique aponeurosis. Recurrence and chronic pain are the usual complications. Instead of the classical incision a mini incision approach through superficial inguinal ring was contemplated. Methods: The study group comprised of 86 male patients with inguinal hernia during the period 2012-2016. Data regarding patient demographics, type of anesthesia given, operation performed and complications were recoded. The operation was carried under spinal or epidural anesthesia. The superficial inguinal ring was palpated and a transverse incision of 1.5 cms. was made over it. Retractors were applied and a space was created to facilitate lifting of cord stucters. The indirect sac was dissected, ligated and excised. The direct sac was pushed inside. The mesh was sutured to the inguinal ligament by interrupted proline sutres and the other side to the conjoint tendon by retracting the wound. The patients were followed up in the post-operative period. Results: There were 86 men with age range of 22- 65 years ( mean 38.5). On examination, 65 patients had indirecet hernia and 20 had direct inguinal hernia. They were operated under spinal anesthesia and 11 under epidural anesthesia. None of the patients were operated under general, local or regional anesthesia. The incision size at superficial ring and measured at the end of the operation was1.4cm, (range1.2 -2cm). By retracting the margins of the external ring upwards by retractors the spermatic cord could be lifted up easily after lifting up from floor of inguinal canal, the indirect sac could be identified, transfixation, ligation and excision of sac was done without difficulty. In direct inguinal hernia, the sac was not opened and was inverted with non absorbable suture (3-0 silk.). The mesh could be easily passed underneath the external oblique, spread and sutured. 3- sutures could be applied by retracting the external oblique. The mean operation time was 42 minutes (range40-52 minutes).There was no post-operative hematoma or scrotal edema in any of the patients. One patient had wound infection, which was treated by dressings. The mean hospital stay was 4.4 days(range 4-6.5 days).Pain in the post-operative period was 1-2 as per visual analogue scale... There was no hematoma or scrotal edema in any of the patients. During the men follow up period of 48 moths(range 12-60 months),there was no recurrence and patient had chronic pain. Conclusion: Open mesh repair of inguinal hernia with a mini incision over the superficial inguinal ring with retraction, gives adequate exposure to place the mesh and repair the hernia.: